Resilience, Adaptive Peacebuilding and Transitional Justice in Post-Conflict Uganda: The Participatory Potential of Survivors’ Groups - Philipp Schulz; Fred Ngomokwe; Edited by Janine Natalya Clark and Michael Ungar (Cambridge University Press, 2021)
In the aftermath of the more than twenty-year armed conflict between the Lord’s Resistance Army and the Ugandan government, northern Uganda has become a transitional justice laboratory. In response to widespread human rights violations perpetrated by both the rebels and government soldiers, various peacebuilding and transitional justice mechanisms have been put into place. However, many of them are top-down and externally-driven, inaccessible to rural communities and/or irresponsive to diverse experiences and post-conflict needs. In this vacuum of post-conflict assistance, different alternative avenues have emerged at the micro level that ultimately enable war-affected communities to engage with their subjective experiences on their own terms. This chapter specifically focuses on the role of survivors’ support groups. It shows how different types of survivors’ groups, in a creative and participatory manner, enable survivors’ agency and craft spaces for healing, justice making and peace-building, shaped by survivors’ own experiences and needs. Support groups thereby aid survivors in developing adaptive capacities to positively respond to shocks and stressors resulting from mass violence. In this way, these groups also contribute to fostering individual and community resilience.
Keywords: adaptive peace building; agency; local ownership; Lord’s Resistance Army; northern Uganda; peace building; resilience; survivors’ groups; transitional justice